(untitled) (Comparative & International Education Series, 2021)
This chapter critically examines the impacts of the coronavirus pandemic on tertiary education in Nigeria and highlights outstanding indigenous innovations within tertiary institutions prompted by the pandemic. The Coronavirus pandemic and the associated lockdown measures have led to the suspension of in-person instruction and learning in many higher education campuses globally. In Nigeria, school closure has negatively impacted the already fragile educational system, causing further hardships for students—who previously grappled with frequent school closures due to incessant strike actions and unrest. Unlike more developed climes—where schools have quickly transitioned to online teaching, poor infrastructural facilities (ICT and Internet) make online teaching and learning an arduous task for the hundreds of higher institutions present in Nigeria. We offer managerial implications relevant for University administrators and managers towards the development of a workable post-COVID-19 education strategy and response plan. How to cite: Adeyanju, S., Ajilore, O., Ogunlalu, O., Onatunji, A., & Mogaji, E. (2022). Innovating in the face of the COVID-19 pandemic: Case studies from Nigerian universities. In J. S. McKeown, K. Bista, & R. Y. Chan (Eds.), Global higher education during COVID-19: Policy, society, and technology (pp. 104-120). STAR Scholars. https://starscholars.org/product/global-education/